III-Nitride Ultraviolet Emitters Technology and Applications - Kneissl, Michael; Rass, Jens.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a comprehensive overview of the state-of-the-art in group III-nitride based ultraviolet LED and laser technologies, covering different substrate approaches, a review of optical, electronic and structural properties of InAlGaN materials as well as various optoelectronic components. In addition, the book gives an overview of a number of key application areas for UV emitters and detectors, including water purification, phototherapy, sensing, and UV curing. The book is written for researchers and graduate level students in the area of semiconductor materials, optoelectronics and devices as well as developers and engineers in the various application fields of UV emitters and detectors.
Introduction -- Low-defect density AlN and AlGaN on sapphire substrate -- HVPE of low-defect density AlGaN/sapphire templates -- Growth and structural properties of bulk AlN substrates -- Optical properties of AlGaN QWs for UV emitters -- Effect of threading dislocations and point defect on IQE of UV emitters -- Optical polarization and light extraction from UV LEDs -- High-power UV LEDs -- Solar- and visible blind UV photodetectors -- Gain in AlGaN QW laser heterostructures -- AlGaN UV laser diodes -- Water purification with UV LEDs -- Application of UV emitters in phototherapy -- UV emitters in sensing applications -- Applications of LEDs for UV-curing.
Keywords: Optical materials; Lasers; Telecommunication; Semiconductors; Optical Materials; Laser; Microwaves, RF Engineering and Optical Communications; Semiconductors